Assessment of the Ubi powder processing project in Bohol the case of the rural improvement club of Corella - Fuentes, Gertrudes S. (University of the Philippines in the visayas, 2005)
This study aims to assess the status of ubi powder processing in the Province of Bohol. Specifically, it aims : 1) to describe the social-economic profile of the beneficiaries of the ubi powder processing project in Bohol ; 2) identify the management practices employed by the beneficiaries in processing ubi powder ; 3) determine the benefits derived by the beneficiaries from the project, and 4) to determine the problems encountered by the beneficiaries in the implementation of the project. The 14 respondents are members of the Rural Improvement Club of the municipality of Corella who are beneficiaries of the ubi powder-process activities project. The members of the association perform the processing activities and are assisted by the Municipal Agriculture Office in the distribution of their product. They process ubi between January to April or as long as there are still raw ubi available. The average volume of ubi powder production per cycle is between 50-60 kilograms. They produce through orders andsell their product on cash basis and extended credit terms with bakeshop owners. They rely on trade fairs and exhibits to promote their products. Their target markets are bakeries, processors of delicacies, walk in consumers, local tourist who made it as "pasalubong" and hotel and resort operators who served uni-based delicacies to their guests.Various support from government agencies were being extended to the association that includes technology, equipment, capability building programs, financial assistance, and market promotion andlinkages. Only 14% of the respondents perceived that there was no improvement in their socio economic conditions after the implementation of the project because they have increasedtheir production which leads to increase in income. As to income earned by the RIC members, however, only 19% comes from bi production which implies that ubi production is not a majocommodity being produced by the members. There is only a slight increase in income of the association by only 6% in 2003 and 3% in 2004. Survey results showed that the benefits gained by the members of the RIC of Corellaare : the increase in knowledge on ubi production, processing, marketing, and additional income both on the part of the members and theassociation. Among the problems encountered by the RIC members are non cooperation of some members, seasonality of the crop, short shelf life of ubi, lack of ready market outletimprove packaging material, and peak of demands is only during Christmas and special festivities, low price for raw tubers and individual marketing of produce. The ubi powder-processing project is not et sustainable due to the fact that it is a seasonal crop and that they only purchase raw material from its members. They only have a limited area planted to ubi, limited capital and all of them utilize their personal funds to finance the production inputs which are among the reasons why ubi production is still low. The project is not profitable for ,they only have a return on investment (ROI) of only 17.4% which indicates that the association only earned 17.4 centavos for every peso invested. However, with their ubi processing projectmembers of the association can have a sure market of their raw ubi. The association now is equipped with the capabilities to pursue its business however, they still need to further strengthen their linkages in promoting and marketing their product.